PERAN DINAS PARIWISATA DAN KEBUDAYAAN DALAM UPAYA PELESTARIAN TRADISI RANDAI DI KABUPATEN KUANTAN SINGINGI TAHUN 2017 - Anggara, Desprio; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The role of the tourism and culture department in the effort to preserve the randai tradition in Kuantan Singingi Regency in 2017 is still not optimal. This is known from the phenomenon of the lack of facilities and infrastructure for the randai tradition, the lack of communication and publication of the randai tradition, and the lack of attention of the younger generation to the randai tradition. This study aims to determine: (1) the role of the Department of Tourism and Culture in the effort to preserve the Randai tradition in Kuantan Singingi Regency; (2) the factors that hinder the preservation of the randai tradition in Kuantan Singingi Regency. This research is a qualitative research with descriptive method. The data collection technique used is the interview technique. Where the interview data were obtained from five informants. Based on the research findings, it can be concluded that the role of the Department of Tourism and Culture in the effort to preserve the Randai tradition in Kuantan Singingi Regency can be said to have been carried out, because there have been coaching activities in the randai group, and equipment assistance provided to some randai groups. Although there are still some randai groups who have not received proper guidance and assistance. Through the 12 roles of the Department of Tourism and Culture in preserving culture, only two roles have not been implemented properly, namely the role in preparing materials for formulating policies and strategies for cultural preservation, and preparing technical guidelines for cultural preservation.Â Keywords : Service Role, Cultural Preservation, Randai Tradition